Enhancements of Major Aerosol Components Due to Additional HONO Sources in the North China Plain and Implications for Visibility and Haze - 安俊岭 李颖 陈勇 李健 屈玉 汤宇佳 (Advances in atmospheric sciences, 2013)
The Weather Research and Forecasting/Chemistry model （WRF-Chem） was updated by including pho- toexeited nitrogen dioxide （NO2） molecules, heterogeneous reactions on aerosol surfaces, and direct emissions of nitrous acid （HONO） in the Carbon-Bond Mechanism Z （CBM-Z）. Five simulations were conducted to assess the effects of each new component and the three additional HONO sources on concentrations of major chemical components. We calculated percentage changes of major aerosol components and concentration ratios of gas NOy （NOyg） to NOy and particulate nitrates （NO3-） to NOy due to the three additional HONO sources in the North China Plain in August of 2007. Our results indicate that when the three additional HONO sources are included, WRF-Chem can reasonably reproduce the HONO observations. Heterogeneous reactions on aerosol surfaces are a key contributor to concentrations of HONO, nitrates （NO3-）, ammonium （NH＋）, and PM2.5 （concentration of particulate matter of ≤2.5 um in the ambient air） across the North China Plain. The three additional HONO sources produced a -5% -20% increase in monthly mean daytime concentration ratios of NO3-/NOy, a -15%- 52% increase in maximum hourly mean concentration ratios of NO3-/NOy, and a -10% -50% increase in monthly mean concentrations of NOx and NH＋ across large areas of the North China Plain. For the Bohai Bay, the largest hourly increases of NO3- exceeded 90%, of NH＋ exceeded 80%, and of PM2.5 exceeded 40%, due to the three additional HONO sources. This implies that the three additional HONO sources can aggravate regional air pollution, further impair visibility, and enhance the incidence of haze in some industrialized regions with high emissions of NOx and particulate matter under favorable meteorological conditions.